Healthy Pills: A Physical Activity and Meditation Program to Enhance Mental Health and Well-Being in Spanish University Students - Laura García-Pérez; Rosario Padial-Ruz; Mar Cepero-González; José Luis Ubago-Jiménez (Behavioral Sciences)
(1) Background: University students’ mental health (MH) is in crisis due to academic stress, lack of physical activity (PA), and low self-esteem. This study evaluated a 12-week PA and meditation intervention to enhance psychological well-being in Spanish university students. (2) Methods: A quasi-experimental design was used, with a non-randomized control group and pretest-posttest assessments. The study lasted 14 weeks (12 weeks of intervention and two for evaluations). Initially, 149 students were recruited, but the final sample included 136 (82 intervention, 54 control) due to attrition. Participants were selected through convenience sampling, respecting university-established groups. The intervention consisted of six PA sessions (aerobic, cardiovascular, and strength exercises) and six meditation sessions (yoga and mindfulness). Validated questionnaires assessed resilience, psychological distress, self-esteem, mood, personality traits, sedentary behavior, PA levels, and sleep duration. (3) Results: Significant improvements were found in resilience (p < 0.001), depression (p < 0.01), and sleep duration (p < 0.05), with greater mood benefits in men. No major changes were observed in other variables. (4) Conclusions: PA- and meditation-based interventions can improve students’ MH, particularly in key psychological aspects. Further research should explore long-term effects and refine strategies by distinguishing between preventive and therapeutic approaches.